Dispute Settlement Reports 2020. Volume III, Pages 1147-1522 - World Trade Organization (Cambridge : Cambridge University Press, 2022)
The Dispute Settlement Reports are the WTO authorized and paginated reports in English. They are an essential addition to the library of all practicing and academic trade lawyers and a valued resource for students worldwide taking courses in international economic or trade law. DSR 2020: Volume 3 provides the report on "United States - Countervailing Measures on Supercalendered Paper from Canada (WT/DS505)".
Title from publisher's bibliographic system (viewed on 28 Jan 2022).
Keywords: Foreign trade regulation -- Cases; Tariff -- Law and legislation -- Cases; Competition, Unfair -- Cases; Dispute resolution (Law) -- Cases